1984
DOI: 10.1073/pnas.81.21.6808
|View full text |Cite
|
Sign up to set email alerts
|

Viral integration near c-myc in 10-20% of mcf 247-induced AKR lymphomas.

Abstract: We induced AKR thymomas by injecting retrovirus MCF 247 that we had tagged with a fragment of phage X in its U3 region. About 10-20% of the 26 primary tumors studied showed both rearranged and germline c-myc bands in Southern blots. The rearranged c-myc genes were cloned from two of the tumors and studied by Southern analysis in two others. In all four cases, rearrangement was due to integration of MCF 247 proviruses about 2 kilobases (kb) 5' of the three cmyc exons and in the opposite transcriptional orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
66
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(78 citation statements)
references
References 30 publications
11
66
1
Order By: Relevance
“…1. Most (32 of 40) of the proviral integrations were in the reverse transcriptional orientation to c-myc and were distributed about a median distance 0.7-kilobase (kb) 5' of exon 1, a finding similar to that reported by other workers (3,9,19). Of the eight tumors with colinear proviral integrations, only two of them, with insertions at +0.7 kb and +5.2 kb, were available for analysis in this study.…”
supporting
confidence: 80%
“…1. Most (32 of 40) of the proviral integrations were in the reverse transcriptional orientation to c-myc and were distributed about a median distance 0.7-kilobase (kb) 5' of exon 1, a finding similar to that reported by other workers (3,9,19). Of the eight tumors with colinear proviral integrations, only two of them, with insertions at +0.7 kb and +5.2 kb, were available for analysis in this study.…”
supporting
confidence: 80%
“…Sequencing of the 1.5-kb region containing the c-myc breaktomas (58) and is also the site of proviral insertion in murine point cluster reveals several regions of homology between the T-cell lymphomas (7,25,44,57) and in Moloney-virusrat, mouse, and human sequences. The breakpoint localizainduced rat thymomas (52).…”
Section: Methodsmentioning
confidence: 99%
“…Since the provirus appeared to have inserted into an intron sequence, the presence of both splice donor and acceptor sites in the vector could have led to alternative splicing and loss of hprt expression as has been previously shown for the dilute mutation. 4 Alternatively, loss of gene expression may have been caused by viral transcription in the opposite orientation to transcription of the hprt gene by the LHL virus, which has also been shown previously to interfere with c-myc oncogene expression, 22 or for the remaining mutants not examined here, provirus insertion(s) within putative hprt promoter/enhancer regions outside the hprt locus may have occurred. Several novel Retrovirus insertional mutagenesis of V79 cells M Themis et al DNA fragments also identified by Southern analysis in coculture-infected mutants using the hprt cDNA probe may have been the result of recombination events between integrated LHL proviruses.…”
Section: à5mentioning
confidence: 66%